Long‐term outcomes in patients with obesity and renal disease after sleeve gastrectomy. Issue 2 (16th November 2019) - Kassam, Al‐Faraaz; Mirza, Ahmad; Kim, Young; Hanseman, Dennis; Woodle, E. Steve; Quillin, Ralph C.; Johnson, Bobby L.; Govil, Amit; Cardi, Michael; Schauer, Daniel P.; Smith, Eric P.; Diwan, Tayyab S.
Abstract : Morbid obesity is a barrier to kidney transplant in patients with end‐stage renal disease (ESRD). Laparoscopic sleeve gastrectomy (SG) is an increasingly considered intervention, but the safety and long‐term outcomes are uncertain. We reviewed prospectively collected data on patients with ESRD and chronic kidney disease (CKD) undergoing SG from 2011 to 2018. There were 198 patients with ESRD and 45 patients with CKD (stages 1‐4) who met National Institutes of Health guidelines for bariatric surgery and underwent SG; 72% and 48% achieved a body mass index of ≤ 40 and ≤ 35 kg/m 2, respectively. The mean percentages of total weight loss and excess weight loss were 18.9 ± 10.8% and 38.2 ± 20.3%, respectively. SG reduced hypertension (85.8% vs 52.1%), decreased antihypertensive medication use (1.6 vs 1.0) ( P  < .01 each), and reduced incidence of diabetes (59.6% vs 32.5%, P  < .01). Of the 71 patients with ESRD who achieved a body mass index of ≤ 40 kg/m 2, 45 were waitlisted and received a kidney transplant, whereas 10 remain on the waitlist. Mortality rate after SG was 1.8 per 100 patient‐years, compared with 7.3 for non‐SG. Patients with stage 3a or 3b CKD exhibited improved glomerular filtration rate (43.5 vs 58.4 mL/min, P  = .01). In conclusion, SG safely improves transplant candidacy while providing significant, sustainable effects on weight loss, reducing medical comorbidities, and possibly improving renal function in stage 3 patients. Abstract : Patients with end‐stage renal disease and who are obese who undergo sleeve gastrectomy have significant weight loss and improvements in comorbidities, helping improve transplant candidacy. An editorial by Orandi and Locke is on page 329 .